Blowing the lid off! Bottle-directed, extractive foraging strategies in synurbic bonnet macaques Macaca radiata in southern India - Pal, Arijit; Mahato, Santanu; Leca, Jean-Baptiste; Sinha, Anindya (Frontiers in Psychology, 2022)
Nonhuman individuals and groups, living in anthropogenic landscapes, often adopt human-induced adaptive foraging strategies, mediated by their day-to-day interactions with humans and their artefacts. Exploring such novel adaptations and their behavioural manifestations, especially in the Anthropocene, offers us insights into more-than-human behavioural innovations and their transmission in such rapidly changing ecologies. In this study, employing field experiments, we investigated an example of human-induced, extractive foraging behaviour – the extraction of liquid food contents from plastic bottles – in a synurbic bonnet macaque Macaca radiata population. The main aims of the study were to examine the distribution, diversity, inter-individual variability and intra-individual flexibility of bottle-directed manipulative behaviours, and to explore the social and environmental factors driving this behavioural practice. We video-recorded the manipulation of partially filled plastic bottles and the extraction of liquid across four groups of bonnet macaques in southern India. Two socio-demographic factors – age class and group membership – and one environmental factor – food provisioning – were identified as major determinants of inter-individual variation in the performance of sophisticated manipulative techniques and in bottle-opening success. Our results also suggest that age-related physical maturation, experiential trial-and-error learning, and possibly social learning contributed to the acquisition of foraging competence in this task. These findings illuminate the mechanisms underlying inter-individual behavioural variability and intra-individual behavioural flexibility amongst free-ranging individuals of a cercopithecine primate species, traditionally known for its ecological adaptability and behavioural plasticity. Finally, this study documents how the presence of humans, their artefacts and their activities facilitate the development and appearance of certain behavioural traditions in free-ranging nonhuman populations, thus providing valuable insights into how human–alloprimate relations can be restructured within the increasingly resource-competitive environments of the Anthropocene.